Demographic Variables Influencing Bullying Conducts Among In-School Adolescents in Ilorin Metropolis - Hassan, Abdulhafis Adeyinka; Owoyale-Abudlganiy, Ibrhaim Solahudeen; Tiamiyu, Kamoru Abidoye (Coution: Journal Counseling and Education, 2025)
This study explored demographic variables influencing bullying behaviours among secondary school students in Ilorin metropolis. A descriptive survey design targeted 42,288 public and private secondary school students across Ilorin Metropolis. A total of 150 respondents were selected to participate in the study. Data was collected using the Olweus Bully/Victim Questionnaire Revised version, which consists of 14 items on a 5-point Likert scale with a reliability coefficient of 0.781. Three null hypotheses were formulated and tested using the t-test statistical tool and analysis of variance (ANOVA) on SPSS. The findings related to the formulated hypotheses examined the significance of gender, age and class differences on bullying behaviour among in-school adolescents in Ilorin metropolis. The result of the findings revealed that there was no significant difference in the bullying conduct of in-school adolescents in terms of age. Also, no significant difference was found based on gender and class level. The study concluded that bullying conduct among in-school adolescents did not show a significant difference based on demographic variables. Therefore, teachers and school staff should receive regular training on identifying and addressing bullying behaviour in students of all ages. This training can include strategies for recognizing forms of bullying, such as verbal and emotional abuse, and techniques for fostering inclusive classroom environments where all students feel safe and supported.